(untitled) (World Science, 2020)
The article devoted to analyzing cinematic entertainment and connections between traditional techniques and computer graphics technologies. Have been analyzed the historical development and the popularity of computer graphics and digital effects. Have been identified difference between special and visuals effects, revealed the most popular techniques at the filmmaking, such as scale modelling, animatronics, stop-motion, slow-motion, time lapse, and the main of tracking methods − motion capture, match-moving, deepfake, also chroma- and lumakey. Have been revealed of their essence. All methods and techniques are compared by the number of highly qualified specialists involved, the budget spent, the time of creation and the audience’s attention. Determined the most popular and effective visual method for viewers. Have been identified the perspectives of computer graphics and digital visual effects. Identified the relevance of combining computer graphics with footage.